Influence of Rural-Urban Migration on Food Insecurity in Cameroon - Chuo Joshua Njuh; Bime MaryJuliet Egwu; Mbu Daniel Tambi (Law and Economy, 2022)
In Cameroon, rural-urban migration is widespread. This paper, therefore, aimed to verify the influence of rural-urban migration on food insecurity in Cameroon. This study makes use of quantitative research design precisely a survey design in which it helps the researcher in gaining insight of the subject matter and familiarity for later investigation using the Cameroon household consumption surveys (ECAM 4, 2014). The dataset has distinctive information on rural-urban migration which was exploited for the composition of a food Insecurity index was also constructed using six indicators; being unable to eat three square meals a day, unable to eat series and tuber every day, unable to eat vegetables every day, unable to eat meat and fish every day, eat good meals only on feast days and unsatisfied with household minimum food needs. The control function approach was used to estimate rural-urban migration and food insecurity. Findings from the empirical indicates that rural-urban migration has a negative. The results also reveal a negative significant relationship between farm investment and food Insecurity in Cameroon. As a result of these findings, it is recommended that there should be an all-inclusive agricultural programme by the government that will engage the farming population to discourage them from further migration from the rural communities.